Metal cord-rubber composite
Patent Information
- Application Number
- JP2023132141
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-14
- Publication Date
- 2025-02-27
AI Technical Summary
【0021】 本発明によれば、ゴム組成物と金属コードとの接着性、耐劣化性及び耐亀裂性を向上させた金属コード-ゴム複合体を提供することができる。
Smart Images

Figure 2025027383000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a metal cord-rubber composite. [Background technology]
[0002] Conventionally, in rubber articles that require strength, such as tires for automobiles, industrial belts, rubber crawlers, etc., metal cord-rubber composites formed by coating a metal cord, such as a steel cord, with a rubber composition have been used for the purpose of reinforcing the rubber to improve its strength and durability. Here, in order for such metal cord-rubber composites to exert a high reinforcing effect, it is necessary to stably and strongly adhere the metal cord to the rubber composition.
[0003] For example, in a pneumatic tire, which is a typical example of a rubber article, a rubber composite in which a steel cord, which is made of a plurality of brass-plated steel wires twisted together or a single steel wire, is coated with rubber, is applied to the belt or carcass, and the steel cord is mainly used for reinforcement. In order to use the steel cord as a reinforcing material for the tire, the steel cord needs to be securely bonded to the rubber coating, and for this reason, the peripheral surface of the wire constituting the steel cord is plated with brass (copper: Cu, Zn). That is, a metal cord such as a brass-plated steel cord is coated with a rubber composition containing sulfur, and the rubber composition is vulcanized and bonded to the metal (rubber-metal adhesive layer (Cu x In the past, various studies have been conducted to improve the adhesiveness between metal cords and rubber in direct vulcanization adhesion. For example, to vulcanize and mold a tire within a certain time, it is necessary to ensure sufficient adhesion between the cord and rubber by fast adhesion and complete bonding between them. In other words, since so-called initial adhesion is required, it is necessary to add a considerable proportion of cobalt-containing compounds such as Co salts or nickel-containing compounds such as Ni salts as adhesion promoters to the rubber, or to compound a high proportion of sulfur.
[0004] However, when a cobalt-containing compound such as a Co salt is compounded with rubber, there are serious problems with physical properties such as rubber deterioration and crack growth resistance compared to rubber that does not contain Co. Therefore, in addition to adjusting the composition of the rubber composition, various proposals have been made regarding metal cords such as wires that are to be bonded to rubber.
[0005] For example, Patent Document 1 discloses a cord-rubber composite comprising a steel cord and a rubber coating, the steel cord being a heat-treated cord using a steel wire that has been plated and then heat-treated at a heating temperature of 400 to 800°C for a heating time of 30 to 250 seconds, and the coating rubber being a rubber composition containing 0.3 to 1.0% moisture in an unvulcanized state (see Patent Document 1). Patent Document 2 discloses a rubber-steel cord composite comprising a rubber composition containing 0.01 to 10 parts by weight, calculated as the metal content, of an organic acid metal salt component that is made of at least one organic acid metal salt and has a metal molar ratio of nickel to molybdenum of 2 / 1 to 20 / 1 per 100 parts by weight of the rubber component, and a brass-plated steel cord with a copper content of 60 to 70% by weight (see Patent Document 2). [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2004-306788 A [Patent Document 2] JP 2005-193793 A Summary of the Invention [Problem to be solved by the invention]
[0007] However, in the rubber and cord composites disclosed in Patent Documents 1 and 2, etc., when used in applications such as large tires, it was difficult to control the deterioration resistance of the rubber while maintaining adhesion due to the usage environment of heavy loads and high internal pressures.
[0008] Therefore, an object of the present invention is to solve the above-mentioned problems of the conventional technology and to provide a metal cord-rubber composite having improved adhesion, deterioration resistance, and crack resistance between a rubber composition, which is a coating rubber, and a metal cord such as a steel cord. [Means for solving the problem]
[0009] The essential features of the metal cord-rubber composite of the present invention that solves the above problems are as follows.
[0010] [1] A metal cord-rubber composite comprising a metal cord coated with a rubber composition, The rubber composition includes a rubber component, carbon black, an amine-based antioxidant, and a quinoline-based antioxidant, and may or may not include a cobalt-containing compound; the rubber composition has a total content of the amine-based antioxidant and the quinoline-based antioxidant of 1.5 parts by mass or more per 100 parts by mass of the rubber component, The rubber composition is a metal cord-rubber composite, in which the content of the cobalt-containing compound, calculated as cobalt, is 0 part by mass or more and 1 part by mass or less per 100 parts by mass of the rubber component. The metal cord-rubber composite described in [1] above has improved adhesion between the rubber composition and the metal cord, as well as improved resistance to deterioration and cracking.
[0011] [2] The metal cord-rubber composite according to [1], wherein the amount of the carbon black in the rubber composition is 50 parts by mass or more and 65 parts by mass or less per 100 parts by mass of the rubber component. The metal cord-rubber composite described in [2] above has improved crack resistance.
[0012] [3] The metal cord-rubber composite according to [1] or [2], wherein the carbon black has an iodine adsorption of 81 mg / g or more and 95 mg / g or less and a DBP absorption of 70 ml / 100 g or more and 80 ml / 100 g or less. The metal cord-rubber composite described in [3] above has an improved balance of crack resistance, heat build-up and modulus.
[0013] [4] The metal cord-rubber composite according to [2], wherein the amount of the carbon black in the rubber composition is 57 parts by mass or more and 65 parts by mass or less per 100 parts by mass of the rubber component. The metal cord-rubber composite described in [4] above has improved crack resistance.
[0014] [5] The metal cord-rubber composite according to any one of [1] to [4], wherein the rubber composition has a sulfur content of 6 parts by mass or less per 100 parts by mass of the rubber component. The metal cord-rubber composite described in [5] above has improved resistance to deterioration.
[0015] [6] The metal cord-rubber composite according to any one of [1] to [5], wherein the rubber composition has a total content of the amine-based antioxidant and the quinoline-based antioxidant of 2 parts by mass or more per 100 parts by mass of the rubber component. The metal cord-rubber composite described in [6] above has improved breaking elongation after aging.
[0016] [7] The metal cord-rubber composite according to any one of [1] to [6], wherein the content of the quinoline-based antioxidant in the rubber composition is 0.5 parts by mass or more per 100 parts by mass of the rubber component. The metal cord-rubber composite described in [7] above has improved breaking elongation after aging.
[0017] [8] The metal cord-rubber composite according to any one of [1] to [7], wherein the amine-based antioxidant is N-(1,3-dimethylbutyl)-N'-phenyl-para-phenylenediamine. The metal cord-rubber composite described in [8] above has improved adhesion after aging.
[0018] [9] The metal cord-rubber composite according to any one of [1] to [8], wherein the quinoline-based antioxidant is poly(2,2,4-trimethyl-1,2-dihydroquinoline). The metal cord-rubber composite described in [9] above has improved breaking elongation after aging.
[0019]
[10] The metal cord-rubber composite according to any one of [1] to [9], wherein the metal cord has a surface N atomic content of 2 atomic % or more and 60 atomic % or less, and a Cu / Zn ratio, on a mass basis, of 1 or more and 4 or less. The metal cord-rubber composite body described in
[10] above has excellent adhesion between the metal cord and the rubber composition.
[0020]
[11] The metal cord-rubber composite according to any one of [1] to
[10] , wherein the single wire of the metal wire constituting the metal cord has a peripheral surface plated with brass, and the brass plating composition contains 40% by mass or more and 80% by mass or less of Cu and 20% by mass or more and 60% by mass or less of Zn. The metal cord-rubber composite body described in
[11] above has excellent adhesion between the metal cord and the rubber composition. Effect of the Invention
[0021] According to the present invention, it is possible to provide a metal cord-rubber composite having improved adhesion, deterioration resistance, and crack resistance between the rubber composition and the metal cord. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] The metal cord-rubber composite body of the present invention will be illustrated and described in detail below based on embodiments thereof.
[0023] <Definition> The compounds described herein may be derived in whole or in part from fossil sources, from biological sources such as plant sources, from recycled sources such as used tires, or from a mixture of two or more of fossil sources, biological sources, and / or renewable sources.
[0024] In this specification, the expression "a to b" in the explanation of a numerical range means that the range is from a to b, unless otherwise specified.
[0025] <Rubber composition> The metal cord-rubber composite is formed by coating a metal cord with a rubber composition. The rubber composition includes a rubber component, carbon black, an amine-based antioxidant, a quinoline-based antioxidant, and optionally includes a cobalt-containing compound. The rubber composition may also include other components in addition to the above components.
[0026] (Rubber component) The rubber component is not particularly limited, and examples thereof include diene rubbers such as natural rubber (NR), butadiene rubber (BR), isoprene rubber (IR), styrene-butadiene copolymer rubber, acrylonitrile-butadiene copolymer rubber, ethylene-propylene copolymer rubber, ethylene-propylene-diene terpolymer rubber, butyl rubber, halogenated butyl rubber, alkylated chlorosulfonated polyethylene rubber, isobutylene-isoprene copolymer rubber, and chloroprene rubber (CR). These rubber components may be used alone or in combination of two or more. For example, natural rubber and isoprene rubber may be used in combination.
[0027] In the rubber composition, the content of the rubber component is not particularly limited and may be a predetermined amount, for example, 80 parts by mass of natural rubber and 20 parts by mass of isoprene rubber per 100 parts by mass of the rubber component.
[0028] (Carbon Black) The rubber composition contains carbon black, which contributes to improving the crack resistance of the metal cord-rubber composite.
[0029] In the rubber composition, the carbon black content is preferably 50 parts by mass or more and 65 parts by mass or less per 100 parts by mass of the rubber component. If the carbon black content is 50 parts by mass or more, the crack resistance of the metal cord-rubber composite is good, and if the carbon black content is 65 parts by mass or less, an increase in heat build-up and modulus of the metal cord-rubber composite can be suppressed. From the viewpoint of improving the crack resistance of the metal cord-rubber composite, the carbon black content is more preferably 57 parts by mass or more and 65 parts by mass or less, and even more preferably 60 parts by mass or less, per 100 parts by mass of the rubber component.
[0030] The carbon black preferably has an iodine adsorption of 81 mg / g to 95 mg / g and a DBP absorption of 70 ml / 100 g to 80 ml / 100 g. When the iodine adsorption and DBP absorption of the carbon black are within the above ranges, a balance between crack resistance, heat generation, and modulus can be achieved. The iodine adsorption amount of carbon black can be measured, for example, in accordance with JIS K 6217-1. The DBP absorption amount of carbon black can be measured, for example, in accordance with JIS K 6217-4:2017.
[0031] The carbon black is not limited, but examples thereof include HAF, HAF-LS, FEF, and GPF grade carbon black. The carbon black may be used alone or in combination of two or more kinds.
[0032] (Anti-aging agent) The rubber composition contains an amine-based antioxidant and a quinoline-based antioxidant. In the present invention, the rubber composition contains the two types of antioxidants, which can improve adhesion between the metal cord and the rubber composition.
[0033] In the rubber composition, the total content of the amine-based antiaging agent and the quinoline-based antiaging agent is 1.5 parts by mass or more per 100 parts by mass of the rubber component. When the total content of the amine-based antiaging agent and the quinoline-based antiaging agent is within the above range, adhesion and crack resistance can be improved. From the viewpoint of adhesion and crack resistance, the total content of the amine-based antiaging agent and the quinoline-based antiaging agent is more preferably 2 parts by mass or more per 100 parts by mass of the rubber component. In addition, for adhesion and production workability, the total content of the amine-based antiaging agent and the quinoline-based antiaging agent is preferably 4 parts by mass or less, more preferably 3 parts by mass or less, per 100 parts by mass of the rubber component.
[0034] The rubber composition may contain an antioxidant other than the amine-based antioxidant and the quinoline-based antioxidant, for example, a phenol-based or imidazole-based antioxidant.
[0035] -Amine-based anti-aging agent- The amine-based antioxidant is an antioxidant having an amine moiety or a derivative thereof, which improves adhesion and crack resistance after aging.
[0036] The content of the amine-based antiaging agent in the rubber composition is preferably 0.5 parts by mass or more and more preferably 1 part by mass or more per 100 parts by mass of the rubber component from the viewpoint of durability, and is preferably 2 parts by mass or less and more preferably 1.8 parts by mass or less per 100 parts by mass of the rubber component from the viewpoint of rolling property.
[0037] As the amine-based antiaging agent, N-(1,3-dimethylbutyl)-N'-phenyl-para-phenylenediamine is particularly preferred. The amine-based antiaging agent may contain an amine-based antiaging agent other than N-(1,3-dimethylbutyl)-N'-phenyl-para-phenylenediamine, and may be used alone or in combination of two or more kinds.
[0038] -Quinoline-based anti-aging agent- The quinoline-based antioxidant is an antioxidant having a quinoline moiety or a derivative thereof (such as a dihydroquinoline moiety), and improves the breaking elongation after degradation.
[0039] The content of the quinoline-based antioxidant in the rubber composition is preferably 0.5 parts by mass or more, more preferably 0.6 parts by mass or more, per 100 parts by mass of the rubber component from the viewpoint of maintaining a certain level of breaking elongation even after deterioration, and is preferably 1.5 parts by mass or less, more preferably 1 part by mass or less, per 100 parts by mass of the rubber component from the viewpoint of rolling properties.
[0040] As the quinoline-based antioxidant, poly(2,2,4-trimethyl-1,2-dihydroquinoline) is particularly preferable. The quinoline-based antiaging agent may contain a quinoline-based antiaging agent other than poly(2,2,4-trimethyl-1,2-dihydroquinoline), and may be used alone or in combination of two or more kinds.
[0041] (Cobalt-containing compounds) The rubber composition may or may not contain a cobalt-containing compound, and the content of the cobalt-containing compound in terms of cobalt is 0 part by mass or more and 1 part by mass or less per 100 parts by mass of the rubber component. The cobalt-containing compound has conventionally been blended as an adhesion promoter in the rubber composition of a metal cord-rubber composite. In this embodiment, from the viewpoint of improving heat deterioration resistance and crack resistance, the content of the cobalt-containing compound in terms of cobalt is 0 parts by mass or more and 1 part by mass or less per 100 parts by mass of the rubber component. From the same viewpoint, the content of the cobalt-containing compound in terms of cobalt is preferably 0 parts by mass or more and 0.1 parts by mass or less per 100 parts by mass of the rubber component, and from the viewpoint of the environment, it is more preferable that the cobalt-containing compound is not contained (i.e., 0 parts by mass per 100 parts by mass of the rubber component).
[0042] Examples of the cobalt-containing compound include cobalt (simple substance), cobalt salts of organic acids, and cobalt salts of inorganic acids. Examples of the cobalt-containing compound include cobalt chloride, cobalt nitrate, cobalt sulfate, cobalt acetate, cobalt citrate, cobalt gluconate, cobalt naphthenate, cobalt neodecanoate, cobalt stearate, cobalt rosinate, cobalt versatate, cobalt tall oil acid, cobalt neodecanoate borate, and cobalt acetylacetonate. The cobalt-containing compound may also be a composite salt in which a part of the organic acid is replaced with boric acid, etc. Examples of the boron-containing organic acid cobalt salt include cobalt orthoborate having a cobalt content of 20 to 23 mass%, and commercially available products include Manobond C22.5 and Manobond 680C manufactured by Rhodia, CoMend A and CoMend B manufactured by Jhepherd, and YYNBC-II manufactured by Dainippon Ink and Chemicals, Inc.
[0043] (sulfur) The rubber composition may contain sulfur. The content of the sulfur in the rubber composition is preferably 6 parts by mass or less per 100 parts by mass of the rubber component. When the content of sulfur is 6 parts by mass or less per 100 parts by mass of the rubber component, deterioration resistance can be improved. In addition, from the viewpoint of maintaining adhesion, the content of sulfur is preferably 3 parts by mass or more, more preferably 4 parts by mass or more, per 100 parts by mass of the rubber component.
[0044] (resin) The rubber composition may contain a resin, the amount of which is preferably 0.1 part by mass or more and 2 parts by mass or less per 100 parts by mass of the rubber composition.
[0045] The resin is not particularly limited, and various resins can be used, such as alkylphenol formaldehyde.
[0046] (Other Ingredients) In addition to the above-mentioned components, the rubber composition may contain other components (other components) that are generally used in the rubber industry, as long as they do not impede the object of the present invention. Examples of other components include vulcanizing agents, fillers such as silica, oils such as process oil, vulcanization accelerators, softeners, zinc oxide, and stearic acid.
[0047] (Method of manufacturing rubber composition) The rubber composition of the present embodiment can be produced by kneading the above components, heating, and extruding them in a conventional manner.
[0048] <Metal cord> The metal cord-rubber composite of this embodiment is formed by coating a metal cord with a rubber composition. The metal cord is formed by twisting together a plurality of metal wires (metal steel wires) or a single metal wire.
[0049] In the present embodiment, the metal wire used is not particularly limited, but examples thereof include wire materials of iron, steel (stainless steel), lead, aluminum, copper, brass, bronze, Monel metal alloy, nickel, zinc, etc. Examples of such metal wires include steel wires. The metal wire preferably has a plating layer formed by a conventional method on its surface. The plating layer is not particularly limited, but examples thereof include a zinc plating layer, a copper plating layer, and a brass plating layer. Among these, a brass plating layer is preferred in terms of initial adhesion to the rubber composition, thermal adhesion, and the formation of a suitable rubber-metal adhesive layer. The bulk brass plating composition constituting the brass plating layer preferably contains 40% by mass or more and 80% by mass or less of Cu (copper) and 20% by mass or more and 60% by mass or less of Zn (zinc) from the viewpoints of steel cord processability and adhesion to rubber, and more preferably contains 55% by mass or more and 70% by mass or less of Cu and 30% by mass or more and 45% by mass or less of Zn.
[0050] As an example of the metal wire, a steel wire will be described in more detail. The steel wire is a linear metal whose main component is steel, i.e., iron (the mass of iron with respect to the total mass of the metal steel wire exceeds 50 mass%). The metal may contain metals other than the above-mentioned iron. From the viewpoint of workability and durability, the steel wire preferably has a wire diameter of 0.1 mm to 5.5 mm, more preferably 0.15 mm to 5.26 mm. Here, the wire diameter of the steel wire refers to the longest length between two points on the circumference of the cross section perpendicular to the axis of the steel wire. The cross section perpendicular to the axis of the steel wire is not particularly limited, and may be elliptical, rectangular, triangular, polygonal, etc., but is generally circular. When a steel cord, which is a metal reinforcing cord in which the steel wires are twisted together, is used for a carcass or belt of a tire, the cross section of the steel wire is preferably circular and the wire diameter is preferably 0.1 mm to 0.5 mm, and when used for a bead core of a tire, the cross section is preferably circular and the wire diameter is preferably 1 mm to 1.5 mm. In addition, the steel wire preferably has a brass plating layer having the above composition on its surface, and the thickness of this plating layer is not particularly limited, but is generally preferably 100 to 300 nm, for example.
[0051] In this embodiment, the N (nitrogen) atomic amount on the surface of the metal cord is preferably 2 atomic % or more and 60 atomic % or less, and the Cu / Zn ratio is preferably 1 or more and 4 or less, based on mass, in terms of treat leaveability, and more preferably, the N atomic amount on the surface of the metal cord is preferably 2.1 atomic % or more and 55.0 atomic % or less, and the Cu / Zn ratio is preferably 1.1 or more and 3.5 or less. By making the proportion of N atoms on the surface of this metal cord 2 atomic % or more, the effect of the present invention can be sufficiently obtained and the deterioration of the treat leaving property can be suppressed. Also, by making it 60 atomic % or less, the deterioration of the initial adhesion to the rubber can be suppressed. Also, by making the Cu / Zn ratio on the mass basis of the surface of the metal cord 1 or more, the effect of the present invention can be sufficiently obtained and the initial adhesion becomes sufficient, and by making it 4 or less, the initial adhesion becomes good and the heat deterioration property becomes sufficient. In the present invention, the N (nitrogen) atomic content on the surface of the metal cord can be adjusted to 2 atomic % or more and 60 atomic % or less by a suitable combination of, for example, a treatment with a triazole compound (rust inhibitor), specifically, a surface treatment such as contacting with an aqueous solution of a triazole compound, and the Cu / Zn ratio on the surface of the metal cord can be adjusted to 1 or more and 4 or less by, for example, a treatment that suitably combines the pH of an acidic buffer solution and the concentration of an aqueous triazole solution. The lower the pH, the higher the Cu / Zn ratio of the obtained metal cord.
[0052] Examples of the acidic buffer solution include acetate buffer, phosphate buffer, citrate buffer, etc., each having a pH of 5.0 to 7.2, and preferably acetate buffer having a pH of 5.0 to 7.2. When the pH is 5.0 or more, the Cu / Zn ratio can be set to 4 or less, and when the pH is 7.2 or less, the Cu / Zn ratio can be set to 1 or more. When an acetate buffer solution having a pH of 5.0 to 7.2 is used, the surface treatment time with this buffer solution can be set to 0.5 to 20 seconds, for example. The triazole aqueous solution may be, for example, an aqueous solution of one or more triazole compounds selected from 1,2,4-triazole, 1,2,3-triazole, 3-amino-1,2,4-triazole, 4-amino-1,2,4-triazole, benzotriazole, tolyltriazole, and 3-mercapto-1,2,4-triazole, and is preferably 1,2,4-triazole, 1,2,3-triazole, 3-amino-1,2,4-triazole, and 4-amino-1,2,4-triazole. The concentration of this triazole aqueous solution is preferably 0.01 to 20 g / L, and the treatment time may be 0.1 to 30 seconds, although it varies depending on the concentration.
[0053] In this embodiment, the "surface" refers to a surface layer region to a depth of 5 (nm) on the radially inner side of a metal wire such as a steel wire. The measurement of N atoms on the surface of the metal cord and the measurement of the Cu / Zn ratio are performed by measuring the surface of the metal cord after the metal cord is obtained and, if necessary, after cleaning and drying, and before it is coated with a rubber composition. In the present invention, the measurement of the amount of N atoms on the surface of the metal cord is performed by measuring the amount of N atoms on the surface of the metal cord using X-ray photoelectron spectroscopy (XPS), and the measurement of the Cu / Zn ratio on the surface of the metal cord is performed by measuring the Cu / Zn ratio on the surface of the metal cord using the photoelectron spectroscopy.
[0054] (Metal Cord Manufacturing Method) In the present invention, for example, by twisting together a plurality of metal wires such as steel wires having the above-mentioned brass plating applied to the peripheral surface, for example, into a 1×N structure such as a 1×2 structure, a 1×3 structure, or a 1×5 structure, or an M+N structure such as a 1+5 structure, a 1+6 structure, or a 2+3 structure, a metal cord made of steel cord can be obtained by a conventional method. The metal cord suitable for reinforcing rubber articles, such as the steel cord, is preferably at least one type selected from the group consisting of belt cords, carcass cords and bead cords for tires.
[0055] <Metal cord-rubber composite> The metal cord-rubber composite of this embodiment is a metal cord-rubber composite obtained by coating a metal cord with a rubber composition, wherein the rubber composition contains a rubber component, carbon black, an amine-based antioxidant, and a quinoline-based antioxidant, and may or may not contain a cobalt-containing compound, and the rubber composition is characterized in that the total content of the amine-based antioxidant and the quinoline-based antioxidant is 1.5 parts by mass or more per 100 parts by mass of the rubber component, and the rubber composition has a cobalt-equivalent content of the cobalt-containing compound of 0 parts by mass or more and 1 part by mass or less per 100 parts by mass of the rubber component. The metal cord-rubber composite can improve the adhesion between the rubber composition and the metal cord, as well as the deterioration resistance and crack resistance.
[0056] (Metal Cord-Rubber Composite Manufacturing Method) The metal cord-rubber composite of this embodiment can be produced by subjecting the metal cord that has been subjected to each of the above-mentioned surface treatments to a cleaning treatment by a conventional method, if necessary, and then bonding the metal cord to the above-mentioned coating rubber composition. By adhering the metal cord having the above-mentioned properties to the rubber composition after the above-mentioned surface treatment, for example, the metal cord and the rubber composition can be vulcanized and bonded under pressure and heat. The vulcanization conditions are not particularly limited, but the pressure is preferably 2 MPa to 15 MPa, more preferably 2 MPa to 5 MPa, and the temperature is preferably 120 to 200° C., more preferably 130 to 170° C. The vulcanization time is not particularly limited, but is preferably 3 minutes to 60 hours.
[0057] The metal cord-rubber composite exhibiting the above-described synergistic effect of this embodiment is not particularly limited in its application, and can be widely used in various rubber products and parts, such as tires for automobiles, power transmission belts, industrial belts such as conveyor belts, rubber crawlers, hoses, and rubber bearings for seismic isolation. In particular, the metal cord-rubber composite of the present invention can be applied as a reinforcing material for tire components such as tire plies (carcass ply, belt ply), bead components, etc. The resulting tire is not particularly limited except that the metal cord-rubber composite of the present invention is used, and the configuration of a known tire can be adopted as it is. A ply to which the metal cord-rubber composite is applied is preferably used as a carcass ply or a belt ply of a tire, and further, the rubber-metal composite is preferably used for tire beads, etc. Similarly, the metal cord-rubber composite is preferably used for industrial belts such as power transmission belts and conveyor belts, rubber crawlers made of rubber mounted on endless track drive devices used in bulldozers, hoses, rubber bearings for seismic isolation, etc. These tires, industrial belts, rubber crawlers, etc. are unlikely to peel off due to excellent adhesive strength and crack growth resistance between the rubber composition and the metal cord, and therefore have excellent durability and a long life despite a high load. EXAMPLES
[0058] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples in any way.
[0059] <Preparation of metal cord-rubber composite> A steel cord with a 1×3 structure was produced by twisting together brass-plated steel wires (plating layer thickness 0.2 μm, wire diameter 0.3 mm) as shown in Table 1 below (such a brass-plated cord is referred to as a brass cord). Next, this cord was washed using the treatment solution consisting of the following treatment methods: Treatment 1: acetate buffer solution or phosphoric acid treatment solution, and Treatment 2: rust inhibitor (triazole compound), and then dried at 50° C. for 1 minute to produce a steel cord.
[0060] -Metal cord measurement- The N amount (outermost surface N amount: atomic %) and Cu / Zn ratio (outermost surface Cu / Zn ratio) on the wire plating surface of the steel cord after the cleaning treatment were measured using an X-ray photoelectron spectrometer (Quantera, manufactured by ULVAC-PHI, Inc.) under the following measurement conditions. X-ray source: Monochromatic Al-Kα radiation Measurement area: 50μmΦ Measured peaks: C1s, O1s, N1s, P2p, Cu2p2 / 3, Zn2p2 / 3 Data processing: Multipak (ULVAC-PHI, Inc.) Quantitation: Quantitation using the relative response coefficient method from the peak area obtained *Cu / Zn is the ratio of the quantitative values of Cu2p2 / 3 and Zn2p2 / 3. The measurement results showed that the outermost surface N amount (atomic %) was 14 atomic %, the outermost surface Cu / Zn ratio was 1.8, and the bulk plating composition (Cu / Zn mass ratio) was 63 / 37.
[0061] - Treatment 1: Treatment with acetate buffer - The treatment with the acetate buffer solution was carried out by washing the steel cord with a treatment solution prepared by adjusting 0.1N sodium acetate to pH 6.6 with acetic acid for a treatment time of 10 seconds.
[0062] - Treatment 2: Treatment with triazole compounds (rust inhibitors) - The treatment with a triazole compound (rust inhibitor) was performed by washing the steel cord with an aqueous solution of the triazole compound, which had been adjusted to a concentration of 10 g / L using 1,2,4-triazole, for a treatment time of 10 seconds.
[0063] The steel cords that had been subjected to the above cleaning treatment (the cords that had been subjected to the above cleaning treatment are referred to as MSC cords) were arranged in parallel at intervals of 12.5 mm, covered with a rubber composition having the compounding recipe shown in Table 1 below, and vulcanized at 145°C for 80 minutes to bond the rubber composition and the steel cords. In this way, a metal cord-rubber composite was obtained in which the steel cords were embedded in a rubber sheet of 1 mm in thickness (the steel cords were arranged at intervals of 12.5 mm on the surface of the sheet at the center in the thickness direction of the rubber sheet).
[0064] <Evaluation of metal cord-rubber composite> The deterioration resistance, adhesion, and crack resistance of the metal cord-rubber composite were evaluated as follows. In Table 1, Brass stands for Brass cord, and MSC stands for MSC cord.
[0065] (Evaluation of deterioration resistance) (1) Breaking elongation before degradation (Eb before degradation) The breaking elongation of the produced metal cord-rubber composite was measured in accordance with JIS K6251. The larger the value, the greater the breaking elongation before degradation.
[0066] (2) Breaking elongation after aging (Eb after aging) The prepared metal cord-rubber composite was aged at 70°C, 0.2 MPa, and in an oxygen atmosphere for 11 days, after which the breaking elongation was measured in accordance with JIS K6251. A larger value indicates a larger breaking elongation after degradation.
[0067] (3) 100% modulus after aging (M100 after aging) The prepared metal cord-rubber composite was aged for 11 days in an oxygen atmosphere at 70° C. and 0.2 MPa, and then the 100% modulus after aging was measured in accordance with JIS K6251. The closer the value is to 6.0, the better the 100% modulus after aging.
[0068] (Evaluation of Adhesion) (1) Heat-degraded adhesiveness The prepared metal cord-rubber composites were aged at 120°C in a nitrogen atmosphere for 28 days, and then the steel cords were pulled out from the metal cord-rubber composites of each Example and Comparative Example, and the coverage of the rubber adhering to the steel cord was determined as 0 to 100% by visual observation in accordance with ASTM D 2229. The results are shown as the time until the coverage rate reached 50%, and are expressed as an index with the value of Comparative Example 1 being 100. A larger index value indicates better heat deterioration resistance adhesion.
[0069] (2) Water-oxygen deterioration adhesion The prepared metal cord-rubber composite was aged for 7 days in an atmosphere of 60°C and 85% relative humidity, and then the steel cord was pulled out from the metal cord-rubber composite of each Example and Comparative Example, and the coverage of the rubber adhering to the steel cord was determined by visual observation as 0 to 100% in accordance with ASTM D 2229. The results are shown as the time until the coverage rate reached 50%, and are expressed as an index with the value of Comparative Example 1 being 100. A larger index value indicates better water and oxygen degradation resistance adhesion.
[0070] (3) Oxygen-degraded adhesiveness The prepared metal cord-rubber composites were aged for 7 days in an oxygen atmosphere at 80°C and 0.2 MPa, and then the steel cords were pulled out from the metal cord-rubber composites of each Example and Comparative Example, and the coverage of the rubber adhering to the steel cord was determined as 0 to 100% by visual observation in accordance with ASTM D 2229. The results are shown as the time until the coverage rate reached 50%, and are expressed as an index with the value of Comparative Example 1 being 100. A larger index value indicates better oxygen degradation adhesion.
[0071] (Evaluation of crack resistance) (1) Crack resistance before deterioration The produced metal cord-rubber composite was subjected to a constant stress fatigue test using a fatigue tester (manufactured by Shimadzu Corporation) to measure the number of cycles until breakage. The results are expressed as an index, with the value of Comparative Example 1 being 100. A larger value indicates better crack resistance.
[0072] (2) Crack resistance after deterioration The metal cord composite thus produced was degraded for 11 days under an oxygen atmosphere at 70°C and 0.2 MPa, and then subjected to a constant stress fatigue test using a fatigue testing machine (manufactured by Shimadzu Corporation) to measure the number of cycles until breakage. The results are expressed as an index, with the value of Comparative Example 1 being 100. A larger value indicates better crack resistance.
[0073] [Table 1]
[0074] *1 NR: Natural rubber (RSS#3) *2 IR: Isoprene rubber (manufactured by ENEOS Materials Corporation, product name "IR2200") *3 Carbon black: Asahi Carbon Co., Ltd., product name "Asahi #70L", iodine adsorption capacity: 81mg / g, DBP absorption capacity: 75ml / 100g *4 Resin: Alkylphenol formaldehyde (manufactured by SI GROUP-RIBEZCOURT, product name "Alkylphenol formaldehyde resin") *5 Bisphenol-based antioxidant: 2,2'-methylenebis(6-tert-butyl-p-cresol) (manufactured by Ouchi Shinko Chemical Industry Co., Ltd., product name "Nocrac NS-6") *6 Amine-based antioxidant: N-(1,3-dimethylbutyl)-N'-phenyl-para-phenylenediamine (manufactured by Ouchi Shinko Chemical Industry Co., Ltd., product name "Nocrac 6C") *7 Quinoline-based antioxidant: Poly(2,2,4-trimethyl-1,2-dihydroquinoline) (manufactured by Seiko Chemical Co., Ltd., product name "Nonflex RD-S") *8 Stearic acid: hydrogenated fatty acid (manufactured by NOF Corporation, product name "Hydrogenated Fatty Acid") *9 Cobalt-containing compound: Cobaltate (manufactured by DIC, product name "Cobalt Versatate", cobalt content: 14% by mass) *10 Vulcanization accelerator A: Manufactured by Ouchi Shinko Chemical Industry Co., Ltd., product name "Noccela CZ", N-cyclohexyl-2-benzothiazolyl sulfenamide *11 Vulcanization accelerator B: Manufactured by Ouchi Shinko Chemical Industry Co., Ltd., product name "Noccela DZ", N,N'-dicyclohexyl-2-benzothiazolyl sulfenamide
[0075] It is apparent from Table 1 above that, compared with Comparative Examples 1 and 2, Examples 1 to 5 have improved adhesion, deterioration resistance, and crack resistance. [Industrial Applicability]
[0076] According to the present invention, it is possible to provide a metal cord-rubber composite having improved adhesion between the rubber composition and the metal cord, resistance to deterioration, and resistance to cracking.
[0077] [Contribution to the United Nations-led Sustainable Development Goals (SDGs)] The SDGs have been proposed to realize a sustainable society. One embodiment of the present invention is considered to be a technology that can contribute to "No. 12_Responsible Consumption and Production" and "No. 13_Concrete measures against climate change."
Claims
1. A metal cord-rubber composite obtained by coating a metal cord with a rubber composition, The rubber composition includes a rubber component, carbon black, an amine-based antioxidant, and a quinoline-based antioxidant, and may or may not include a cobalt-containing compound; the rubber composition has a total content of the amine-based antioxidant and the quinoline-based antioxidant of 1.5 parts by mass or more per 100 parts by mass of the rubber component, The rubber composition is a metal cord-rubber composite, in which the content of the cobalt-containing compound, calculated as cobalt, is 0 part by mass or more and 1 part by mass or less per 100 parts by mass of the rubber component.
2. 2. The metal cord-rubber composite according to claim 1, wherein the amount of the carbon black in the rubber composition is 50 parts by mass or more and 65 parts by mass or less per 100 parts by mass of the rubber component.
3. The metal cord-rubber composite according to claim 1, wherein the carbon black has an iodine adsorption of 81 mg / g or more and 95 mg / g or less and a DBP absorption of 70 ml / 100 g or more and 80 ml / 100 g or less.
4. The metal cord-rubber composite according to claim 2, wherein the amount of the carbon black in the rubber composition is 57 parts by mass or more and 65 parts by mass or less per 100 parts by mass of the rubber component.
5. 2. The metal cord-rubber composite according to claim 1, wherein the rubber composition has a sulfur content of 6 parts by mass or less per 100 parts by mass of the rubber component.
6. 2. The metal cord-rubber composite according to claim 1, wherein the rubber composition has a total content of the amine-based antioxidant and the quinoline-based antioxidant of 2 parts by mass or more per 100 parts by mass of the rubber component.
7. 2. The metal cord-rubber composite according to claim 1, wherein the content of the quinoline-based antioxidant in the rubber composition is 0.5 parts by mass or more per 100 parts by mass of the rubber component.
8. 2. The metal cord-rubber composite according to claim 1, wherein the amine-based antioxidant is N-(1,3-dimethylbutyl)-N'-phenyl-para-phenylenediamine.
9. 2. The metal cord-rubber composite according to claim 1, wherein the quinoline-based antioxidant is poly(2,2,4-trimethyl-1,2-dihydroquinoline).
10. 2. The metal cord-rubber composite according to claim 1, wherein the metal cord has a surface N atomic amount of 2 atomic % or more and 60 atomic % or less, and a Cu / Zn ratio of 1 or more and 4 or less on a mass basis.
11. The metal cord-rubber composite according to claim 1, wherein the single metal wire constituting the metal cord is brass-plated on the peripheral surface thereof, and the brass plating composition is 40% by mass or more and 80% by mass or less of Cu and 20% by mass or more and 60% by mass or less of Zn.
Citation Information
Patent Citations
Cord-rubber complex and pneumatic tire using it
JP2004306788A
Rubber-steel cord combined and pneumatic tire
JP2005193793A